The Impact of Sustainable Supply Chain Management, Service Innovation, and Product Innovation on Customer Satisfaction with Competitive Advantage as a Mediating Variable in a Telecommunications Company: The Impact of Sustainable Supply Chain Management, Service Innovation, and Product Innovation on Customer Satisfaction with Competitive Advantage as a Mediating Variable in a Telecommunications Company - Raymond, Sihar; Nusraningrum, Dewi (IJOSMAS, 2025)
This study analyzes the impact of Sustainability Supply Chain Management (SSCM), Service Innovation, and Product Innovation on Competitive Advantage and Customer Satisfaction at PT X, with Competitive Advantage as a mediating variable. Data from 71 respondents were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results show that SSCM positively affects Customer Satisfaction (p-value = 0.000) but does not impact Competitive Advantage (p-value = 0.606). Service Innovation has no significant effect on either Competitive Advantage or Customer Satisfaction (p-value = 0.303 and p-value = 0.363). Product Innovation negatively affects Competitive Advantage (p-value = 0.001) but positively impacts Customer Satisfaction (p-value = 0.000). Competitive Advantage mediates the relationship between Product Innovation and Customer Satisfaction (p-value = 0.033), but does not mediate the relationship between SSCM and Customer Satisfaction or Service Innovation and Customer Satisfaction. These findings suggest that PT X should focus on product innovation to enhance competitive advantage, while improving sustainability and service innovation communication to maximize customer satisfaction